Leite instável não ácido em bovinos : ocorrência, efeito do teor de álcool e qualidade de acordo com estações do ano - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Unstable non-acidic milk (LINA) occurs in dairy herds and is characterized by changes in the physical and chemical characteristics of the milk. The main change identified is the loss of casein stability to the alcohol test, resulting in positive precipitation, without high milk acidity. The objective was to evaluate the occurrence of LINA under different concentrations of alcohol content and the effect of LINA under the milk quality characteristics of mixed breed animals. A total of 272 samples were collected from eight municipalities in western Goiás during the four seasons of the year. The titratable acidity tests were performed and of alcohol (72%, 74%, 76%, 78% and 80%) pH, density, cryoscopy, casein, fat, crude protein, lactose, total dry extract, number of somatic cells, and ethanol, and total bacterial count. The results were submitted to analysis of variance and the means were compared using the Tukey test at 5% probability. The highest occurrence of LINA was in the autumn and winter seasons, being, that the alcoholic graduation, influenced proportionally, the phenomenon incident. Regarding milk components in the winter season there was a reduction in protein and fat contents, comparing LINA milk to normal milk. The CBT and CCS showed higher counts in the summer period. It is concluded that the occurrence of LINA changes the compositional characteristics of the milk and that the alcohol level determines a larger number of samples unstable to the alizarol test.
Keywords: Alizarol; Estabilidade; Componentes do leite; Alizarol. .; Milk components; Stability; CIENCIAS AGRARIAS